Comparison of a 5‐mm and 10‐mm vessel sealing device in an open ovariectomy model in dogs. (29th April 2017) - Devriendt, N.; Van Goethem, B.; Van Brantegem, L.; De Ridder, M.; Kitshoff, A.; Or, M.; de Rooster, H.
Abstract : The objectives of this study were to compare (1) the extent of thermal damage and (2) the time between the 5‐mm LigaSure V (LS5) and 10‐mm LigaSure Atlas (LS10) vessel sealing devices (VSD) when performing open ovariectomy in dogs. A prospective, randomised, clinical trial was performed in 40 client‐owned sexually entire female dogs. In each dog, one ovary was randomly assigned to be surgically removed using LS5 and the contralateral using LS10. The depth of thermal spread, measured on histopathological preparations, was significantly larger for LS10 (LS10 1.35±0.23 mm v LS5 0.82±0.10 mm; P<0.001). Mean ovariectomy time was significantly faster when using LS10 (LS5 2.58±1.32 minutes v LS10 2.07±1.27 minutes; P=0.008). Bodyweight was positively correlated with the time required for ovariectomy using LS5 (P=0.004), but no such correlation was present for LS10 (P=0.611). In conclusion, during open ovariectomy using VSD, LS10 causes significantly more thermal spread but surgical time is shorter compared with LS5. When using LS5, the ovariectomy time increases with increasing bodyweight.